Slightly crosslinked polyurethane with Diels–Alder adducts from trimethylolpropane. Issue 39 (26th June 2016) - Du, Pengfei; Jia, Haiyan; Chen, Qinghua; Zheng, Zhen; Wang, Xinling; Chen, Denglong
ABSTRACT: Diels–Alder (DA) reactions between furan and maleimide have been widely applied in thermally remendable polymeric materials. Crosslinked polyurethane with DA adducts exhibited much better mechanical properties than linear polyurethane with DA adducts. However, the highly crosslinked polyurethane needs a higher temperature and a longer healing time. This will increase the possibility of side reactions proceeding during the healing procedure. In this paper, slightly crosslinked polyurethane with DA adducts was synthesized by incorporating trimethylolpropane into linear polyurethane with DA adducts. The structure of the intermediate and final products was characterized by Fourier transform infrared spectroscopy, 1 H‐NMR, and differential scanning calorimetry, confirming that the synthesizing process proceeded successfully. The images from the polarizing optical microscope demonstrated that the final product with slight crosslinking needed less time and a lower healing temperature to complete the healing procedure. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43971. Abstract :